2018
DOI: 10.1172/jci.insight.98811
|View full text |Cite
|
Sign up to set email alerts
|

Frameshift events predict anti–PD-1/L1 response in head and neck cancer

Abstract: Programmed cell death protein 1 (PD-1) inhibitors have efficacy in treating squamous cell carcinoma of the head and neck (SCCHN), but objective response rates are low. PD-1 ligand (PD-L1) expression alone is not considered a robust predictor of response and additional biomarkers are needed. This 3-year observational cohort followed 126 SCCHN patients treated with anti-PD-1/L1 therapy. Prior to treatment, 81 (64%) had targeted massively parallel tumor sequencing. Of these, 42 (52%) underwent fluorescence-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
182
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(201 citation statements)
references
References 42 publications
9
182
3
Order By: Relevance
“…The association between high TMB and improved outcomes in the current study may reflect immunogenic potential -whereby high TMB facilitates neoantigen recognition and a resulting immunologic response to attack the tumor. But independent of TMB, HPV + patients appear to have higher response rates to immune checkpoint blockade (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between high TMB and improved outcomes in the current study may reflect immunogenic potential -whereby high TMB facilitates neoantigen recognition and a resulting immunologic response to attack the tumor. But independent of TMB, HPV + patients appear to have higher response rates to immune checkpoint blockade (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…In evaluating the molecular landscape of metastatic HPV tumors, we first assessed TMB, a measure of total mutation events in the coded genome, as it holds significant promise as a biomarker for response to immunotherapy (24). Our own work has recently shown that TMB is lower among virally mediated recurrent head .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV status was predictive of improved response to durvalumab . Furthermore, a higher number of some subtypes of tumor‐infiltrating lymphocytes (TILs), such as PD‐1 + TIM‐3 + CD8 + TILs and PD‐1 + LAG‐3 + CD8 + TILs, and higher tumor mutation burden (TMB) and CD8 + TILs, all predicted improved response to anti‐PD‐1 or anti‐PD‐L1 therapies …”
Section: Biomarkers In Hnscc Tumor Tissuesmentioning
confidence: 99%
“…122 Furthermore, a higher number of some subtypes of tumor-infiltrating lymphocytes (TILs), such as PD-1 + TIM-3 + CD8 + TILs and PD-1 + LAG-3 + CD8 + TILs, and higher tumor mutation burden (TMB) and CD8 + TILs, all predicted improved response to anti-PD-1 or anti-PD-L1 therapies. 133 Several recent conference presentations have also highlighted novel data regarding predictive biomarkers in the era of immunotherapy ( Table 2). For example, PD-1 + CD8 + effector T cells and PD-1 + Treg cells in tumor tissue predicted response to nivolumab, 136 whereas mutational load and IFN-γ gene expression profile (GEP) predicted response to pembrolizumab.…”
Section: Predictive Tissue Markers For Egfrtargeted Therapymentioning
confidence: 99%